Pengaruh Pencatatan, Pelaporan Dan Pengawasan Terhadap Kinerja Sektor Publik Pada Dinas Pendidikan Kabupaten Wajo - Burhanuddin Burhanuddin; Basri Modding; Darwis Lannai (Public Service and Governance Journal, 2023)
This study aims to analyze the effect of recording, reporting and monitoring on public sector performance, and analyze the dominant influence between recording, reporting and monitoring on public sector performance. This type of research is quantitative which is designed to answer the problems that have been formulated and the objectives to be achieved as well as to test hypotheses. The population is all employees of the Wajo District Education Office. The sample size was selected using purposive, namely the employees of the financial management division who were determined as many as 97 respondents. Data analysis used descriptive analysis and multiple linear regression analysis. The results of the study found that recording had a significant effect on public sector performance. This shows that the apparatus in the financial management section of the Wajo District Education Office has carried out budget records in accordance with the applicable mechanism, starting from recording income, spending and proposed changes to the budget, which have contributed to improving the performance of the public sector. Reporting has a significant effect on the performance of the public sector. This means that officials in the financial management section of the Wajo District Education Office have made reports on the budget based on realization, balance sheet, operations, cash flow and equity on the budget in a transparent manner towards improving public sector performance. Supervision has a significant effect on the performance of the public sector. This shows that the financial management section of the Wajo District Education Office carries out monitoring activities of budget allocations in the form of transfers, financing and changes in balances over the budget contributing to improving public sector performance. Reporting is the dominant variable that has a significant effect on the performance of the public sector. This means that reporting activities carried out by officials in the financial management section of the Wajo District Education Office determine the achievement of public sector performance based on input, process, output, outcome, benefit and impact.